Impact of chorionicity on first‐trimester nuchal translucency screening in ART twin pregnancies. (29th April 2013) - Flöck, A.; Reinsberg, J.; Berg, C.; Gembruch, U.; Geipel, A.
ABSTRACT: Objective: Nuchal translucency (NT) measurement in assisted reproduction treatment (ART) twins is less extensively investigated. Therefore, the present study compared NT measurements of spontaneously conceived twins with ART twins in dichorionic (DC) and monochorionic (MC) pregnancies. Methods: Retrospective analysis of 706 unaffected twins between 11 + 0 and 13 + 6 weeks conceived either spontaneously ( n = 362) or with ART ( n = 344). The group with spontaneous conception included 234 DC (64.6%) and 128 MC (35.4%) pregnancies. In the ART group, 326 were DC (94.7%) and 18 were MC (5.3%). NT values were transformed into multiples of median (MoM). Results: In the DC group, no significant differences between ART and spontaneously conceived twins (NT MoM 1.06 ± 0.28 vs 1.03 ± 0.29; p > 0.05) were observed. NT MoM of MC ART twins was higher compared with spontaneous MC twins (1.23 ± 0.82 vs 0.99 ± 0.27; p = 0.011). Although the incidence of twin‐to‐twin transfusion syndrome (TTTS) was higher among ART twins (11.1% vs 4.7%), inter‐twin NT difference was similar between pregnancies with TTTS (0.42 ± 0.21) or without (0.40 ± 0.71). Conclusions: Measurement of NT thickness in DC ART twins achieves comparable results with twins conceived spontaneously. Conclusions in MC twins are limited; however, higher NT MoM was not related to TTTS or selective intrauterine growth restriction. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Measurement of nuchal translucency (NT) is an effective and validated method to detect chromosomal abnormalities in singletons and twins. Most studies reported comparable screening results in assisted reproduction treatment (ART) singletons compared with spontaneous conceptions. However, ART twins are less extensively investigated, especially with respect to chorionicity. What does this study add? This study is the first analysis about the impact of chorionicity on NT screening in ART and spontaneous twins in a large cohort.